Strategi Pengembangan Metode Pengajaran melalui Platform Daring di POLTEKPAR Bali - Lukia Zuraida; Isa Wahjoedi Dwi P (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2022)
This study aims to find strategies for developing online teaching methods at POLTEKPAR Bali. Data were obtained by observing and interviewing lecturers and students who attended online class. The data shows that this method has strengths and weaknesses on internal factors and external factors. SWOT analysis is used to determine online teaching development strategies. The results of the analysis of the strengths, weaknesses, opportunities and threats that exist in internal and external factors show that the online teaching method has a total IFE value of 3.1 and a total EFE value of 2.7 and is in quadrant 1, and needs to be developed with SO, WO, ST and WT strategy. The SO strategy consists of the need for training for lecturers, making teaching standards, through the online system the teaching and learning process can still be carried out as a face-to-face substitute, teaching data is well integrated, utilizing facilities. WO strategies include monitoring lecturers for students, training and teaching standards online systems, motivating students, making interesting teaching materials. ST strategies include lecturers having to understand information technology, make good preparations, continue to strive for the continuity of the teaching and learning process, creatively make interesting teaching materials, and institutions monitor the performance of lecturers and vice versa. WT strategies include making interesting materials to motivate students, improving lecturers' information technology knowledge, training related to online learning, monitoring student attendance, and building good communication, motivating students to be more interactive.